Southward-Directed Subduction of the Farallon–Aluk Spreading Ridge and Its Impact on Subduction Mechanics and Andean Arc Magmatism: Insights From Geochemical and Seismic Tomographic Data - Iannelli, Sofía B.; Fernández Paz, Lucía; Litvak, Vanesa D.; Gianni, Guido; Fennell, Lucas M.; González, Javiera; Lucassen, Friedrich; Kasemann, Simone; Oliveros, Verónica; Folguera, Andrés (Frontiers in Earth Science, 2020)
Since the initial proposal of the past existence of a southward-directed mid-ocean ridge–subduction interaction in the Andes during Late Cretaceous–Paleogene times, several studies have been devoted to uncover the tectonomagmatic evidence of this process. The collision of a spreading ridge against a subduction margin provokes important tectonomagmatic changes, including, between them, variations in arc-related magmatic activity and in the plate-margin stress regime. However, the cryptic nature of the geological record often hampers assessing the influence and along-strike evolution of this process. In this study, we integrate new isotopic data with previous field and geochemical data on Andean arc-related magmatism, together with seismic tomography to track the main tectonic changes that affected the Andes between 35° and 42°S from Latest Cretaceous to early Miocene times. In particular, we carry out a new tomotectonic analysis combining the regional bedrock record of the Late Cretaceous–early Miocene arc with upper–lower mantle seismic tomography. This analysis allowed us to unravel the main geodynamic changes that affected the Andean active-margin when the Farallon–Aluk spreading ridge was subducting. Besides, new isotopic analyses reveal the variable nature of the mantle source that fed the Late Cretaceous–early Miocene arc. Hence, the integration of geological, geochemical, and geophysical data, together with new isotopic data studying the geochemical composition of the main Andean arc-related magmatic units in three main periods – (1) Latest Cretaceous–early Paleocene, (2) Early Paleocene–late Eocene, and (3) Late Eocene–early Miocene – allow us to understand with an unprecedented detail the geochemical and spatiotemporal evolution of the passage of this spreading ridge along the Andean margin.